2016
DOI: 10.1515/hukin-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric Training on Physical Fitness in Team Sport Athletes: A Systematic Review

Abstract: Plyometric training (PT) is a very popular form of physical conditioning of healthy individuals that has been extensively studied over the last decades. In this article, we critically review the available literature related to PT and its effects on physical fitness in team sport athletes. We also considered studies that combined PT with other popular training modalities (e.g. strength/sprint training). Generally, short-term PT (i.e. 2-3 sessions a week for 4-16 weeks) improves jump height, sprint and agility p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 67 publications
4
100
1
4
Order By: Relevance
“…Markovic showed moderate‐to‐high effects of PLY on four different vertical jump tests, while Stojanovic showed moderate effects on CMJ in amateur, collegiate, and elite female athletes. Similar results were shown in youth soccer athletes and young team‐sport athletes …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Markovic showed moderate‐to‐high effects of PLY on four different vertical jump tests, while Stojanovic showed moderate effects on CMJ in amateur, collegiate, and elite female athletes. Similar results were shown in youth soccer athletes and young team‐sport athletes …”
Section: Discussionsupporting
confidence: 86%
“…Existing literature reviews, evaluating PLY interventions, have reported that PLY can improve vertical jump height and sprint performance . Furthermore, studies report improved neuromuscular function as well as more specific neural adaptations such as increased motor unit activation . PLY has also been implemented effectively in the rehabilitation of injured athletes, where the primary focus is on lower body control and correct mechanics with progression toward high‐intensity plyometric exercises to resolve postinjury neuromuscular impairments and prepare the musculoskeletal system for rapid movements and high forces similar to the demands imposed in sports .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations